Efektivitas teknik diskusi dalam bimbingan kelompok untuk membantu dalam perencanaan karir siswa - Albertus Hengka Nove; Agus Basuki; Sunaryo Al Idha Sunaryo (Jurnal Konseling dan Pendidikan, 2021)
This study aims to test the hypothesis of "effective discussion techniques in group guidance to help students’ career planning". This experimental research used the one group pretest – posttest model. A total of 10 participants were selected using purposive sampling based on certain considerations. The career planning instrument with 25 statement items was used to collect data from each participant. The validity and reliability of the instrument were ensured using the construct validity test with the supervisor. The study was conducted in 3 meetings, while the analysis was carried out using paired samples test. The average posttest score is greater than the pretest score and the results show that there is a significant difference in the attitude of students toward career planning before and after participating in group guidance with discussion techniques. Hence, it can be concluded that effective discussion techniques are effective to improve students’ attitude toward career planning.